DFT Study of Electronic and Ionic Transport in Li₃VBPO₇ for Cathode Materials - El Macouti, Nour El Haq; El Bouanounou, Mohamed; Assila, Abdelmajid; Hlil, El Kebir; Boughaleb, Yahia; Hajjaji, Abdelowahed; Laasri, Said (Z͡H︡urnal inz͡h︡enernykh nauk, 2025)
The increasing demand for high-performance lithium-ion batteries (LIBs) necessitates novel cathode materials with enhanced electronic and ionic transport properties. This study aims to evaluate the potential of Li3VBPO7 as a cathode material using density functional theory (DFT) with the CASTEP code, focusing on its electronic structure and lithium diffusion characteristics. Based on a monoclinic structure with lattice parameters (a = 5.0581 Å, b = 6.4127 Å, c = 16.9708 Å), the analysis reveals a 0.8 eV band gap in the pristine state, transitioning to 0 eV during lithium migration, indicating enhanced electronic conductivity. Nudged elastic band calculations yield a low activation energy of 0.29 eV with a diffusion coefficient of about 1.7 10–12 m2/s and ionic conductivity of about 2.31·10–4 S/m at 300 K, suggesting efficient lithium transport. As a result, geometry optimization confirmed structural stability, while population analysis highlighted ionic bonding. These properties position Li3VBPO7 as a promising cathode for high-rate LIBs, with potential applications in electric vehicles and grid storage, pending experimental validation through synthesis and electrochemical testing.